(untitled) (Comillas Journal of International Relations, 2021)
Through policies of media control, changes in the legal framework, sanctions and arrests of critical journalists, Nicolás Maduro, Venezuela’s president since 2013, has established a regime of censorship in the country, where freedom of press is practically non-existent. This paper evaluates the relevance of censorship in the permanence of the Maduro regime: if it is increasingly easy to evade censorship measures, why does the regime continue to survive? It will be found that, even though there are numerous policies of information restriction, they do not manage to prevent the creation of critical spaces. However, the mere existence of these spaces, due to their own limitations, will not pose enough of a challenge to the regime’s permanence. Fake news, political bots or corruption in the country will be some of the factors that will limit the best functioning of these spaces and will contribute to the regime’s continued survival.